PERAN KEPEMIMPINAN TRANFORMASIONAL DAN PEMBERDAYAAN TERHADAP KOMITMEN ORGANISASIONAL DENGAN MEDIASI KEPUASAN KERJA (STUDI PADA DINAS PERINDAG PROVINSI JATENG) - 10.42.02.0129, M. Rr. Toetoet Hajoeningtias (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this study to examine the effect of transformational leadership and empowerment on organizational commitment through employee satisfaction. The study was conducted by taking object on the employees in the Department of Industry of Central Java Province. Data was collected using surveys, using purposive sampling, with the minimum criteria tenure of 3 years, which amounts to 85 people. Analysis of Linear Regression is used. The hypothesis has been demonstrated only 4 of 5 hypothesis, so there are 1 unsupported hypothesis. The study found that organizational commitment can be achieved in two ways, namely (1) is influenced directly by the leadership, it means that transformational leaders may have reflected the intellectual stimulation turns will be able to create organizational commitment (2) indirectly affected by empowerment through job satisfaction, meaning when employees feel empowered they will feel satisfied of the work, so that they will commit to the organization. Keywords: transformational leadership, empowerment, job satisfaction and organizational commitment